2020
DOI: 10.1155/2020/1896935
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hip Screw with Trochanter-Stabilizing Plate Compared with Proximal Femoral Nail Antirotation as a Treatment for Unstable AO/OTA 31-A2 and 31-A3 Intertrochanteric Fractures

Abstract: Background. The dynamic hip screw (DHS) with the addition of an angular stable trochanter-stabilizing plate (TSP) has been considered the ideal treatment for the unstable intertrochanteric fracture type. However, there have been few comparisons between DHS+TSP augmentation with intramedullary (IM) nailing. The aim of this retrospectively registered study was to compare the clinical outcomes of patients with the unstable type of intertrochanteric fractures treated with DHS+TSP or IM nailing (proximal femoral na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…19 For the recovery of A2 and A3 fractures, the DHS-TSP devices exploited lessening of post-operative reduction of haemoglobin for unstable intertrochanteric fractures, however, accompanied by an increase of residual pain and implant irritation. 20 This perhaps is linked to the additional treatment of trochanteric stabilizing plate that may offer steadier healing in elderly unstable per trochanteric fractures. Hence, the solitary use of sliding hip screws is presumably discouraging due to several reported postoperative complications, including femoral head screw cut out, 21 avascular necrosis of the femoral head, cracking of screws, femoral fracture below the plate, and the development of coxarthrosis and pseudoarthrosis.…”
Section: Resultsmentioning
confidence: 99%
“…19 For the recovery of A2 and A3 fractures, the DHS-TSP devices exploited lessening of post-operative reduction of haemoglobin for unstable intertrochanteric fractures, however, accompanied by an increase of residual pain and implant irritation. 20 This perhaps is linked to the additional treatment of trochanteric stabilizing plate that may offer steadier healing in elderly unstable per trochanteric fractures. Hence, the solitary use of sliding hip screws is presumably discouraging due to several reported postoperative complications, including femoral head screw cut out, 21 avascular necrosis of the femoral head, cracking of screws, femoral fracture below the plate, and the development of coxarthrosis and pseudoarthrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Although nowadays many surgeons prefer intramedullary devices due to its minimally invasive, time-sparing approach as well as theoretically better biomechanical intramedullary load distribution [21], the dynamic hip screw globally is still the most used implant for the treatment of proximal femur fractures. Until now, no superiority of one implant over the other has been clearly demonstrated [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the lateral wall of the femur plays an important mechanical stabilization role in the treatment of femoral fractures, and that the integrity of the lateral wall can provide rotational stability for the femur, support the bone of the head and neck, and effectively resist its varus, rotation, and diaphyseal displacement, which can avoid the cut-out of screws [ 16 , 18 ]. The helical blade must be implanted in the femoral head neck through the lateral wall for FIF, whether treated with extramedullary fixation or intramedullary nailing, and maintaining the integrity of the lateral wall is critical to the stability of FIF internal fixation [ 19 , 20 ]. However, Palm et al [ 21 ] found that 74% of lateral wall fractures were due to intraoperative manipulation, while patients with lateral wall fractures had a 22% re-operation revision rate.…”
Section: Discussionmentioning
confidence: 99%